Factors influencing the completion of extensive reading tasks: A case study of Indonesian students in tertiary EFL class - Fergina, Ana; Oktavianda, Melti (Englisia: Journal of Language, Education, and Humanities, 2024)
Extensive Reading (ER) has received considerable attention in foreign language teaching and learning in Indonesia. However, research on student engagement and completion rates of ER assignments in higher education is limited. This qualitative case study investigates the factors that influence the completion of ER assignments among students in a counselling programme at a state university in Kalimantan. Using semi-structured interviews, the study explores students' perspectives and experiences to gain a comprehensive understanding of the challenges they face in completing extensive reading assignments. The findings reveal a complex interplay of factors that impede task completion, including lack of intrinsic motivation and interest in reading, vocabulary difficulties, and the learning environment. These findings highlight the critical role of English language teachers in creating a motivating and supportive learning environment, providing targeted vocabulary instruction and fostering a reading culture to maximise the benefits of ER for language acquisition and academic success in higher education.